Perceived Level Of Stress And Coping Mechanisms Adopted By Engineering Interns In A Technical University In Malaysia - Nurul Aina, Ramlee (2025)
Stress is a condition that everyone goes through. Engineering interns experience stress during their academic-to-professional environment transition. The study assessed perceived stress levels among engineering interns, the prevalence of coping mechanisms adopted to overcome stress, and the relationship between perceived stress level and coping mechanisms adopted by engineering interns. In a cross-sectional quantitative study, 276 engineering intern’s students from different engineering faculties which involved FTKA, FTKKP, FTKEE, FTKMA and FTKPM were assessed perceived stress level using the Perceived Stress Scale (PSS-10), and coping mechanisms using the Ways of Coping Questionnaire (WOCQ). Spearman's correlation is used to analyse the relationship between engineering interns' perceived stress levels and coping mechanism. The study found that, 70.3% of engineering interns reported moderate stress, 18.1% high perceived stress and 11.6% low stress with differences found across demographic variables like gender (p=0.036). Positive reappraisal was the most common coping mechanisms (mean=13.87), while accepting responsibility was the least used coping mechanisms (mean=7.99). Emotion-focused coping was commonly used by engineering interns to cope with stress (mean=62.73), than problem-focused coping (mean=29.62). The study reported no significant difference in coping mechanisms between gender and faculty with p-value of 0.669 and 0.221 respectively. Spearman’s correlation analysis indicated a weak positive correlation between perceived stress levels and coping mechanisms (r=0.261, p=0.000). As the level of stress increase, engineering interns tend to look for coping mechanisms. Coping mechanisms adopted by engineering interns are also significantly correlated with perceived stress levels. This study suggests using stress management programs to promote stress knowledge and management.